THE ACCURACY OF RISK SCORES IN PREDICTING PRETERM BIRTH : A SYSTEMATIC REVIEW - Syahputra Damanik, Roni Andre (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Around the world, premature birth, also known as preterm birth (PTB), is one of the leading causes of perinatal illness and death. The majority of preterm births (two-thirds) are the result of spontaneous preterm birth (SPTB), while the remaining one-third are necessary for medical reasons owing to complications with either the mother or the fetus. A combination of factors, including a large decline in birth rates and an increase in the average mother age at the time of conception, has led to an increase in the number of pregnancies accomplished with the use of assisted reproductive technology (ART), as well as an increase in the number of children who are delivered prematurely. Despite the enormous advancements that have been achieved in the treatment of premature babies, the prevention of preterm births is not yet a reality. This is despite the fact that there has been substantial success made in treating premature newborns. There are a number of risk factors that have been linked to premature birth, including a cervix that is too short, a maternal age that is larger than 35 years, a maternal body mass index that is greater than 25, smoking habits, and comorbid risk factors (such as hypertension and diabetes).